Bringing data from curated pathway resources to cytoscape with OmniPath - Ceccarelli, Francesco; Turei, Denes; Gabor, Attila; Sáez Rodríguez, Julio (Bioinformatics, 2020)
AbstractSummary. Multiple databases provide valuable information about curated pathways and other resources that can be used to build and analyze networks. Omn
Advance access publication date: 30 December 2019
Gesehen am 25.03.2021